Shakespeare's mature tragedies - McElroy, Bernard (Princeton University Press, 2014)
Despite their diversity in tone and subject matter, Shakespeare's four mature tragedies--Hamlet, Othello, King Lear, and Macbeth--all have an essential experience in common. Bernard McElroy defines this experience as the collapse of the subjective world of the tragic hero. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of t.
Cover.
Keywords: Shakespeare, William, -- 1564-1616 -- Tragedies.; Shakespeare, William, -- 1564-1616; Tragedy.; Tragédie.; tragedies.; tragedy (general genre); DRAMA -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Shakespeare.; Criticism and interpretation; Tragedy